Analyzing the Role of Organizational Culture, Training Effectiveness, Emotional Intelligence, and Employee Motivation on Team Performance - Fitri Melawati (Journal Management & Economics Review (JUMPER), 2026)
This study aims to analyze the role of organizational culture, training effectiveness, emotional intelligence, and employee motivation on team performance. A quantitative research approach with a cross-sectional survey design was employed, involving 250 employees working in team-based organizational environments. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method. The results indicate that all four variables—organizational culture, training effectiveness, emotional intelligence, and employee motivation—have a positive and significant effect on team performance. Among these, employee motivation and emotional intelligence were found to have the strongest influence, highlighting the importance of psychological and behavioral factors in driving team effectiveness. Organizational culture and training effectiveness, while significant, serve as foundational elements that support the development of individual capabilities. The model demonstrates strong explanatory power, suggesting that the integration of organizational and individual factors provides a comprehensive understanding of team performance. This study contributes to the literature by offering an integrated framework and provides practical implications for organizations to enhance team performance through cultural development, effective training, and employee-focused strategies.